ダイ17ジ ナンキョク チイキ カンソクタイ ニヨッテ ショウワ ミズホ キチ デ カンソク サレタ Pc 1ガタ ミャクドウ ノ カイセキ d. ジキケンナイ ノ ULF ハドウ ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 1 - 野崎, 憲朗; ノザキ, ケンロウ; NOZAKI, Kenrou (1980)
P(論文) 昭和基地で,1976年1月から1977年1月までの1年間に観測された,Pc 1地磁気脈動についてそのダイナミックスペクトルを作成した.このデータをもとに,Pc 1の発生時間および地磁気じょう乱との関係を調べた.その結果,発生頻度は午後側に大きなピークを持つ高緯度に特有な日変化パターンを示すことが分かった.また世界的な地磁気じょう乱を表すKp指数とPc 1脈動の相関はよくないが,ring currentの発達を表すDstとはよい相関が認められた.一般に昭和基地とみずほ基地ではスペクトルの形はよく似ているが,一方のステーションでしか観測されない現象もいくつか見出された.また昭和基地で観測された代表的なPc 1現象について偏波解析を行った. Diurnal variations of occurrence frequency of Pc 1 pulsations and relationships between Pc 1 events and Kp, Dst and K (at Syowa Station) indices have been studied by using f-t spectra of magnetic pulsations observed at Syowa and Mizuho Stations during one year from January 1976 to January 1977. It is found that the occurrence probability of Pc 1 events does not depend on the magnitude of Kp index, while there is a tendency that the occurrence probability of Pc 1 events increases greatly when the magnitude of Dst index is larger than -80 nT. It is also found that the f-t spectral patterns of Pc 1 events observed at Syowa and Mizuho Stations were generally quite similar to each other. However, several Pc 1 events were observed only at Syowa Station. Furthermore, dynamic polarization patterns of three typical Pc 1 events observed at Syowa Station are given in this paper. departmental bulletin paper